Music map image mapping / Mohd Ridzuan Othman - Othman, Mohd Ridzuan (2010)
Nowadays, people especially teenager like to hear to modern song which is from various genres such as pop, rock and hip hop. They also influenced by this type of music that indirectly change their attitude, behavior and manner from good to be bad. The worst part is they never know about the traditional folk music because never exposed by mass media. So this project tries to expose to people about traditional folk music using the website that suitable with the current technology. The objective of this project is to develop a prototype that give necessary information about the music and people also can hear the music. The technique used for this project is image mapping as it deal with an image as a link to others web page. Hopefully this project gives benefit to people in order to encourage them to like our traditional folk music in each state in Malaysia. In means time can ensure traditional folk music as digital heritage preservation.